INDUSTRI GENTING SOKKA HAJI ABOENGAMAR DAN PENGARUHNYA TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT KEBUMEN (1917-1938) - Naila Fathia Nufus; Sutiyah Sutiyah (Lambung Mangkurat University, 2026)
This study examines the Sokka Haji Aboengamar roof-tile industry in Kebumen (1917–1938) as a driver of the Bumiputera economy during the colonial era. Originating in the late 19th century utilizing local high-quality clay traditionally, the industry grew rapidly, stimulated by railway infrastructure, government buildings, and plague control policies. The year 1917 marked a turning point in management modernization through mass advertising. This study employs a historical method comprising the stages of heuristics, criticism, interpretation, and historiography. Primary sources include archival reports, colonial newspapers, and company documents. Meanwhile, secondary sources comprise books, articles, and previous research. The results show a transformation in the production process from traditional to modern technology, although production volumes fluctuated due to market dynamics. Mass media marketing expanded the reach of the products. Socio-economically, this industry absorbed thousands of local workers, encouraged the transition from the agricultural to the industrial sector, and contributed to the creation of hygienic residences. Furthermore, partnerships with vocational schools made it a centre for the transfer of mechanisation skills and a model centre for the tile industry in the Dutch East Indies.